Calidad y eficacia de dos metodos no selectivos de recoleccion manual de cafe (Coffea arabica) - Wallis G., J.A.=700 1 Montoya R., E.C.; Velez Z., J.C.; Oliveros T., C.E.
(En, Es)
ilus., 10 ref.
Keywords: COFFEA ARABICA; CAFE; RECOLECCION; COSECHA; METODOS; COLOMBIA